The Connection of Capital Leverage and Profitability by the Corporate Agriculture Enterprises - Herczeg, Adrienn (Acta Agraria Debreceniensis, 2009)
The analysis of capital system of agricultural corporations is a key issue of economics and the effect of it's fluctuation can be observed on several fields of the life of corporations.It influencesfor example the assets-, financial- and income situation of the enterprises.The aim of this study is to analyse the connection between capital structure and profitability in order to reveal sucha ratio for the capital leverage and liabilities, by which it can say, to that connect the profit or loss. By the analyse get activity- and size specified results.With the empyrical results I determine the quantile point between the profitable or the non profitable operating.